The sun is also a star - Yoon, Nicola 1972- (Delacorte Press, 2016)
"Two teens...Daniel, the son of Korean shopkeepers, and Natasha, whose family is here illegally from Jamaica...cross paths in New York City on an eventful day in their lives...Daniel is on his way to an interview with a Yale alum, Natasha is meeting with a lawyer to try and prevent her family's deportation to Jamaica...and fall in love"...
Keywords: JUVENILE FICTION / Social Issues / Emotions & Feelings / bisacsh; Migration; Love; Fate and fatalism; Korean Americans; Jamaican Americans; Illegal aliens; Deportation; Emigration and immigration; JUVENILE FICTION / Social Issues / Emotions & Feelings; Liebe; Schicksal; Einwanderung; Ausweisung; Illegale Einwanderung; New York (N.Y.); Jugendbuch